What Did Augustine Learn about the Old Testament as a Manichaean Hearer? - Moiseeva, Evgenia (Augustinianum, 2024)
St. Augustine initially discovered the Bible through Manichaean eyes, but later engaged in intense anti-Manichaean polemics largely centered on the Old Testament. To shed light on what Augustine learned about the Manichaean approach to the OT during his Manichaean youth, this study gathers and analyzes relevant excerpts from De Genesi aduersus Manichaeos, De moribus ecclesiae catholicae et de moribus Manichaeorum, and Augustine’s testimonies about his Manichaean years in Confessions and De agone christiano. It is shown that Augustine the Manichaean gained extensive knowledge of the Manichaean biblical criticism and was well versed in the Manichaean arguments and polemical strategies. Notwithstanding his own polemical remarks, Augustine was well aware that the Manichaeans did not reject the OT outright and used some vetero-testamentary narratives in their own teaching. The paper also discusses written and oral sources of Augustine’s knowledge of the Manichaean position.